Efficacy, safety, and potential industry bias in using deoxycholic acid for submental fat reduction ‒ A systematic review and meta-analysis of randomized clinical trials - Inocêncio, Gabriel Santiago Giuglio; Meneses-Santos, Daniela; Costa, Marcelo Dias Moreira de Assis; Vieira, Walbert A.; de Almeida, Vinicius Lima; Rodrigues, Renata Prata Cunha Bernardes; Rode, Sigmar de Mello [UNESP]; Paranhos, Luiz Renato (Elsevier, 2023)
Lipolytic substance injections to reduce localized fat have been extensively used because it is a low-invasive method. This review aimed to evaluate the efficacy and safety of deoxycholic acid in submental fat reduction compared to a placebo and investigate the potential industry sponsorship bias in the results of randomized clinical trials on this topic. Ten electronic databases were extensively searched for randomized clinical trials without restriction on language and year of publication. Two reviewers extracted the data and assessed the individual risk of bias in the studies with the RoB 2.0 tool. The industry sponsorship bias was evaluated according to citations in the articles regarding industry funding/sponsorship throughout the texts. Fixed and random effects meta-analyses were performed, and the results were reported in Risk Ratio (RR) at a 95% Confidence Interval (95% CI). The initial search provided 5756 results, of which only five were included. Only two studies had a low risk of bias. All studies showed a potential industry bias. The meta-analysis showed that patients treated with deoxycholic acid had significant positive results for all efficacy outcomes and a higher risk of fibrosis, pain, erythema, numbness, swelling, edema, pruritus, nodules, headache, and paresthesia. The low to moderate certainty of evidence found allows concluding that deoxycholic acid is effective in submental fat reduction, causing well-tolerated adverse effects. However, all eligible studies showed a potential industry bias.
Keywords: Deoxycholate; Deoxycholic acid; Lipolysis